2019
DOI: 10.1149/2.0461913jes
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2,2-Dithiodipyridine as a Leveler for Through-Holes Filling by Copper Electroplating

Abstract: 2,2-dithiodipyridine (DTDP), a low molecular weight nitrogen-containing heterocyclic compound with a disulfide bond, is added as a novel leveler to the plating solution to achieve the void-free filling of through-holes (THs) by butterfly technology (BFT). Herein, quantum chemical calculation and molecular dynamics (MD) simulation theoretically manifest that DTDP can adsorb on the copper surface through its plentiful active sites and strong adsorption capacity, which can provide theoretical support for DTDP as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Meanwhile, a pattern reaction for the synthesis of levelers has not yet emerged. Design and synthesis of levelers are time-consuming, so the study of the structure–property of levelers is of great significance. ,, A previous study reported diketopyrrolopyrrole (DPP)-based levelers which have a fully conjugated, highly stable, and rigid planar structure . A DPP-based leveler with a four-ring-fused skeleton is an excellent substrate that could firmly anchor on the copper surface and optimize the deposition behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, a pattern reaction for the synthesis of levelers has not yet emerged. Design and synthesis of levelers are time-consuming, so the study of the structure–property of levelers is of great significance. ,, A previous study reported diketopyrrolopyrrole (DPP)-based levelers which have a fully conjugated, highly stable, and rigid planar structure . A DPP-based leveler with a four-ring-fused skeleton is an excellent substrate that could firmly anchor on the copper surface and optimize the deposition behavior.…”
Section: Introductionmentioning
confidence: 99%
“…15−17 property of levelers is of great significance. 10,18,19 A previous study reported diketopyrrolopyrrole (DPP)-based levelers which have a fully conjugated, highly stable, and rigid planar structure. 15 A DPP-based leveler with a four-ring-fused skeleton is an excellent substrate that could firmly anchor on the copper surface and optimize the deposition behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The organic additives consist of accelerators [2][3], suppressors [4][5] and levelers [6][7]. Three types of organic additives enhance chemical reactions, improve surface deposition increase the uniformity of thickness and enhance filling with high aspect ratio features and improve the overall plating [8][9][10][11]. Sulfuric acid is used as a highly conductive electrolyte and chloride ions improve the performance of additives.…”
Section: Introductionmentioning
confidence: 99%
“…Because an electro-Cu plating technology is mainly used to form TSV interconnects, 5,6) the electro-Cu plating is a particularly important technology in the TSV process and developments of the electro-Cu plating technology are being advanced. [7][8][9][10][11][12] It is well-known that the Cu crystallite diameter and the crystal grains increase by selfannealing at room temperature. 13,14) This transformation leads to the generation of stress in wire formed by Cu.…”
Section: Introductionmentioning
confidence: 99%